Delivering the faecal occult blood test: More instructions than shared decisions. A qualitative study among French GPs. (September 2013) - Aubin-Auger, Isabelle; Mercier, Alain; Mignotte, Katell; Lebeau, Jean-Pierre; Bismuth, Michel; Peremans, Lieve; Van Royen, Paul
ABSTRACT: Background: Colorectal cancer (CRC) is the third most common cancer worldwide. In France, mass screening has been established with FOBT since 2008. The participation rate remains too low. Previous studies were conducted to explore doctors' and patients' perspectives. Objective: This study was conducted to explore GPs' performance during consultations in which patients ask for FOBT, focusing on two different aspects: the core content of the consultation and the communication style used between GPs and patients. Methods: Nine purposively sampled GPs were asked to audiotape specific consultations. Content analysis was performed using Nvivo 9 software. Communication between doctors and patients was explored using RIAS coding. Results: GPs audio taped specific parts of 35 different consultations when they discussed and delivered the FOBT. The core content included primarily biomedical statements with a large portion dedicated to technical aspects. The communication style was not patient-centred. Conclusion: While the participation rate of mass screening in France is still low, the analysis of recorded consultations by French GPs confirms that the way of delivering FOBT can be improved.